Hydrogen Evolution: The Role of Phosphate Group in Doped Cobalt Molybdate: Improved Electrocatalytic Hydrogen Evolution Performance (Adv. Sci. 12/2020) - Zhao, Siyu (Adv Sci (Weinh), 2020)
In article number 1903674, Guanjie He, Ivan P. Parkin, and co‐workers fabricate self‐standing P‐modified CoMoO(4) materials supported on Ni foam electrocatalyst via a facile hydrothermalannealing method for the hydrogen evolution reaction (HER). The enhanced HER performance and structure‐performance relationship are carefully investigated. [Image: see text]